2018
DOI: 10.1021/acs.jpcc.8b04289
|View full text |Cite
|
Sign up to set email alerts
|

Ice Nanoribbons Confined in Uniaxially Distorted Carbon Nanotubes

Abstract: Water confined inside nanopores exhibits unusual static and dynamic properties that depend on the pore size, pore topology, and hydrophobicity and roughness of the pore walls. The properties also depend on the geometrical shape of the pore cross sections. Here, we investigated water inside distorted single-wall carbon nanotubes (SWCNTs) by means of classical molecular dynamics calculations, over a temperature range of 100–350 K. SWCNTs, which provide ideal one-dimensional cylindrical pores with atomically smoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 45 publications
2
12
1
Order By: Relevance
“…crystallization. In a carbon nanotube, the crystalline structure of water has been recently shown to be distinct from that in bulk 12 .…”
Section: Introductionmentioning
confidence: 99%
“…crystallization. In a carbon nanotube, the crystalline structure of water has been recently shown to be distinct from that in bulk 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, four monolayer ices are recently predicted on the Au-like model substrate with embedded dipoles or quadrupoles . To date, the reported Q2D ice structures include monolayer and bilayer square ices, , bilayer hexagonal and rhombic ices, distorted bilayer hexagonal ice, , bilayer interlocked pentagonal ice, monolayer rhombic ices, ,, helical monolayer ice, and trilayer ice. , Q1D ices reported to date include square, pentagonal, hexagonal, heptagonal, and octagonal single-walled ice nanotubes. ,, MD simulations also showed that more complex Q1D high-density nanoices can exhibit multistranded helical structures when formed at ultrahigh hydrostatic pressure in carbon nanotubes …”
mentioning
confidence: 99%
“…In addition to the 18 bulk ices and three major gas hydrates, quasi-two-dimensional (Q2D) and quasi-one-dimensional (Q1D) ice phases can also be produced in the laboratory through either nanoscale confinement or water vapor deposition at very low temperature. Here, the confinement length scale can be viewed as a new tunable variable that can influence the formation of the overall hydrogen-bonding network of water during the freezing transition. By using molecular dynamics (MD) simulations, Koga et al reported the first evidence of spontaneous formation of Q2D ice (bilayer hexagonal ice) in 1997 and four Q1D ices in 2001 for water confined in hydrophobic slit nanopores and in model carbon nanotubes, respectively.…”
mentioning
confidence: 99%
“…Within natural biological systems, such as AQP1 aquaporin channels, nanoconfined water molecules are arranged in unique one-dimensional (1D) water wires that enable precise mobility and exhibit fast transport rates (3 × 10 9 s –1 per channel). Water is also trapped in the nanoscale pore spaces and channels of geologic materials, such as zeolites, ,, clay minerals, , or sedimentary rocks that result in variable melting point temperatures, density, and surface tension and impact transport behavior . Within engineered systems, behavior of nanoconfined water has been explored in mesoporous silica, ,, carbon nanotubes, graphene sheets, ,, inorganic nanotubes, and lipids, , with all systems exhibiting behavior that diverges from the bulk. These chemical and physical changes are likely dependent on both the size of the pore space and the chemical character of the interior walls.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of hydrophobic pores, carbon-based materials, namely, single-walled carbon nanotubes, have offered the most insight into the system. Due to the repulsion between the interior channel walls and encapsulated water molecules, hydrophobic carbon nanotubes strongly encourage hydrogen-bonding interactions between the nanoconfined water molecules. , , This leads to ordered arrangements of water molecules that have similarities to ice-like arrays, with structural variability occurring due to the overall pore size. , In addition, spontaneous uptake of water and fast mass transport have been reported for these systems because the extended arrays of hydrogen-bonding water networks do not interact strongly with the pore walls. ,,, Strictly hydrophilic pores exhibit strong interactions between the confined water molecules and hydrophilic groups (such as hydroxyl) and can create islands of highly coordinated local water regions that are also more ordered than that of bulk water. , In addition, the liquid–solid phase transition is depressed in hydrophilic environments, with smaller pore sizes (1.5 nm) leading to melting/freezing temperature changes of up to 40 K . Hybrid materials offer an interesting middle ground that can provide variability in these behaviors.…”
Section: Introductionmentioning
confidence: 99%